Asymmetric fluorocyclizations of alkenes. - Wolstenhulme, JR; Gouverneur, V (American Chemical Society, 2014)
Conspectus The vicinal fluorofunctionalization of alkenes is an attractive transformation that converts feedstock olefins into valuable cyclic fluorinated molecules for application in the pharmaceutical, agrochemical, medical, and material sectors. The challenges associated with asymmetric fluorocyclizations induced by F(+) reagents are distinct from other types of halocyclizations. Processes initiated by the addition of an F(+) reagent onto an alkene do not involve the reversible formation of bridged fluoronium ions but generate acyclic β-fluorocationic intermediates. This mechanistic feature implies that fluorocyclizations are not stereospecific. A discontinuity exists between the importance of this class of fluorocyclization and the activation modes currently available to implement successful catalysis. Progress toward fluorocyclization has been achieved by investing in neutral and cationic [NF] reagent development. The body of work on asymmetric fluorination using chiral cationic [NF](+) reagents prepared by fluorine transfer from the dicationic [NF](2+) reagent Selectfluor to quinuclidines, inspired the development of asymmetric F(+)-induced fluorocyclizations catalyzed by cinchona alkaloids; for catalysis, the use of N-fluorobenzenesulfonimide, which is less reactive than Selectfluor, ensures that the achiral F(+) source remains unreactive toward the alkene. These organocatalyzed enantioselective fluorocyclizations can be applied to indoles to install the fluorine on a quaternary benzylic stereogenic carbon center and to afford fluorinated analogues of natural products featuring the hexahydropyrrolo[2,3-b]indole or the tetrahydro-2H-furo[2,3-b]indole skeleton. In an alternative approach, the poor solubility of dicationic Selectfluor bis(tetrafluoroborate) in nonpolar solvent was exploited with anionic phase transfer catalysis as the operating activation mode. Exchange of the tetrafluoroborate ions of Selectfluor with bulky lipophilic chiral anions (e.g., TRIP and derivatives) brings into solution the resulting chiral Selectfluor reagent, now capable of asymmetric fluorocyclization. This strategy is best applied to a subset of substrates bearing a nucleophilic pendent group (benzamide is best) capable of hydrogen bonding for association with the chiral phosphate catalyst. These contributions focused on fluoroheterocyclization involving either O- or N-nucleophiles. As for other halocyclizations, alkenes armed with π C-nucleophiles represent the most demanding class of substrates for asymmetric F(+)-induced electrophilic fluorination-cyclization. Successful implementation required the design of new chiral Selectfluor reagents featuring stereogenicity on the DABCO core. These reagents, accessible from chiral vicinal diamines, allowed the synthesis of unusual chiral fluorine-containing tetracyclic compounds, some composed of carbon, hydrogen, and fluorine exclusively. The challenges associated with F(+)-induced fluorocarbocyclizations prompted methodologists to consider chemistry where the Csp(3)-F bond formation event follows a catalyst-controlled cyclization. An exciting development built on in the area of transition metal π-cyclization of polyenes leading to cationic metal-alkyl intermediates. When intercepted by oxidative fluorodemetalation with a F(+) source, the resulting products are complex polycyclic structures emerging from an overall catalytic cascade fluorocarbocyclization. Complementing F(+)-based reactions, examples of fluorocyclizations with fluoride in the presence of an oxidant were reported. Despite some exciting developments, the field of asymmetric fluorocyclizations is in its infancy and undoubtedly requires new activation modes, catalysts, as well as F(+) and F(-) reagents to progress into general retrosynthetic approach toward enantioenriched fluorocycles. Numerous opportunities emerge, not least the use of a latent fluorine source as a means to minimize background fluorination.